Tribological Mechanism in Chip Formation and Its Use to Improve Machining Process - Vasilko, Karol (Manufacturing Technology Journal, 2019)
It is a well-known fact that during cutting there occurs an extremely high degree of chip plastic deformation. These deformation structures require attention as they influence technical and economical results of cutting (cutting forces, quality of machined surface, tool wear, cutting temperature). Intensive friction between the tool and the chip as well as inside the deformed chip trigger the mechanism of plastic deformation. The paper analyses the mechanism and suggests the possibilities of its use to influence the deformation field inside the chip with the aim to improve cutting process.
Keywords: machining; turning; plastic deformation; tool life; surface quality